1996
DOI: 10.1046/j.1525-1438.1996.06010038.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiation therapy is not necessary in the management of endometrial carcinoma stage I, low-risk cases

Abstract: In an attempt to create uniform nationwide guidelines for the management of all stages of endometrial carcinoma, and to limit the use of adjuvant radiation therapy in stage I disease to high‐risk patients only, a protocol was developed by the Danish Endometrial Cancer group (DEMCA). From September 1986 through August 1988, 1214 women in Denmark with newly diagnosed carcinoma of the endometrium have been treated according to this protocol. This figure represents all endometrial carcinomas diagnosed in Denmark d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 5 publications
3
28
0
1
Order By: Relevance
“…7 Approximately 75% of the cases have stage I disease at diagnosis, and within this stage, tumor grade and myometrial invasion are consistent prognostic indicators of lymph node metastases and survival. 12 In our study 93 (77.4%) patients had FIGO stage I disease. If the myometrium is not invaded, nodal metastases are rare, irrespective of histologic grade.…”
Section: Discussionsupporting
confidence: 42%
“…7 Approximately 75% of the cases have stage I disease at diagnosis, and within this stage, tumor grade and myometrial invasion are consistent prognostic indicators of lymph node metastases and survival. 12 In our study 93 (77.4%) patients had FIGO stage I disease. If the myometrium is not invaded, nodal metastases are rare, irrespective of histologic grade.…”
Section: Discussionsupporting
confidence: 42%
“…The recurrence rate of our high-risk node-negative group (group B) was 15.7%, which is consistent with previous reports (20,29) . The recurrence rate observed by COSA-NZ-UK group was 14% in high-risk patients treated with formal surgical staging and brachytherapy (20) , while the Danish Endometrial Cancer Group demonstrated a 15% recurrence rate in the same group of patients who underwent hysterectomy and pelvic radiotherapy (29) .…”
Section: Discussionsupporting
confidence: 93%
“…The total recurrence rate in low-risk patients in our study was 8.1% (n ¼ 7) of which 5.8% recurred vaginal (n ¼ 5), and they were locally cured with salvage radiotherapy. Because of the 2.3% (2/7) low rate of fatal recurrence in this subset of patients, and because the deaths were due to distant metastases without pelvic relapse after salvage radiotherapy, and because of the high OS and disease-specific survival (93% and 97.5%, respectively), we agree with the previous reports that lowrisk patients are optimally treated by hysterectomy and bilateral salpingo-oophorectomy only (25,28,29) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ces micrométastases sont la source des récidives ganglionnaires tardives couramment observées dans les centres de recours. Enfin, la documentation de l'absence d'atteinte ganglionnaire aide à renoncer à des irradiations externes systématiques [64].…”
Section: Resultsunclassified